The Effect of Tiktok Use on Political Literacy and Political Participation of Student State High School Mumbulsari in the 2024 Regional Head Elections 2024 - Asmorojati, Damar; Murdiono, Mukhamad; Rizal, A (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyse the utilisation of the social media platform TikTok in enhancing political literacy among students at SMA Negeri Mumbulsari. The research questions focus on how the use of TikTok influences students’ political understanding and to what extent their political participation changes after accessing political content on the platform. The method employed is quantitative with an ex post facto approach, involving a sample of 109 Year 12 students. The theoretical framework underpinning this research comprises theories of political literacy and political participation within the context of social media. The findings indicate that TikTok plays a significant role in enhancing students’ political awareness, as demonstrated by the notable increase in their interaction and participation in political discussions. In conclusion, TikTok can serve as an effective political education tool for the younger generation if utilised appropriately.